EVALUASI SLURAN DRAINASE PADA JALAN TLOGO INDAH KELURAHAN TLOGOMAS KECAMATAN LOWOKWARU MALANG - Martins, Marcal; Suhudi, Suhudi; Sulistyani, Kiki Frida (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
The drainage system is needed to dispose of rainwater is not absorbed in the soil, and to prevent puddles of water that can interfere with the activity of the community or cause flooding when the rainy season. Problems puddle into thought and attention from various parties, it is because of the lack of public enthusiasm and lack of drainage channels within and around the District Area Lowokwaro. The research was conducted on the road Tlogo Beautiful Village Tlogomas Lowokwaru District Malang. The method used in this study is a rational method that Qa = 0.278. C. I. A, while the data obtained from the study site is the condition of roads and damaged Existing channel and also the data from several agencies, among others: Data population, the data rainfall, land use map. From the analysis in flood discharge effluent to when ualng 5 years b = 1.028 m3 / s and Q 10 years of h = 1.176 m3 / s. Existing channels in the Tlogo Beautiful Village Tlogomas Lowokwaru District Malang Made of concrete with dimensions b = 0.8 h = 0.8. This channel is to miss out on Q 5 and Q 10 years. To guard against inundation then urged the public not to throw garbage on the channel and conduct routine maintenance by the relevant authorities and the public. Keywords : maximum Daily rainfall data and Existing Channels